Viruses and bacteria in floodplain lakes along a major Amazon tributary respond to distance to the Amazon River - Almeida, Rafael M.; Roland, Fábio; Cardoso, Simone J.; Farjalla, Vinícius F.; Bozelli, Reinaldo L.; Barros, Nathan O. (Frontiers in Microbiology, 2015)
Because of the massive water volume of the Amazon River, the Amazon tributaries have their water backed up by hundreds of kilometers upstream their mouth. This backwater effect is part of the complex hydrodynamics of Amazonian surface waters, which in turn drives the variation in concentrations of organic matter and nutrients, and also regulates planktonic communities such as viruses and bacteria. Viruses and bacteria are commonly tightly coupled, and their ecological role in aquatic food webs has been increasingly recognized. Here, we surveyed viral and bacterial abundances in 26 floodplain lakes along the Trombetas River, the largest clear-water tributary of the Amazon River’s north margin. We correlated viral and bacterial abundances with temperature, pH, dissolved inorganic carbon, dissolved organic carbon (DOC), phosphorus, nitrogen, turbidity, water transparency, partial pressure of carbon dioxide (pCO2), phytoplankton abundance and distance from the lake mouth until the confluence of the Trombetas with the Amazon River. We hypothesized that both bacterial and viral abundances would change along a latitudinal gradient, as the backwater effect becomes more intense with increased proximity to the Amazon River; different flood duration and intensity among lakes and waters with contrasting sources would cause spatial variation. Our measurements were performed during the low water period, when floodplain lakes are in their most lake-like conditions. Viral and bacterial abundances, DOC, pCO2 and water transparency increased as distance to the Amazon River increased. Most viruses were bacteriophages, as viruses were strongly linked to bacteria, but not to phytoplankton. We suggest that bacterial abundances increase in response to DOC quantity and possibly quality, consequently leading to increased viral abundances. Our results highlight that hydrodynamics plays a key role in the regulation of planktonic viral and bacterial communities in Amazonian floodplain lakes.